Desarrollo de estrategias para el fortalecimiento de exportaciones de calzado para dama producido por PYMES asociadas a la cámara de calzado de Tungurahua- Caltu hacia el mercado venezolano. - Espinosa Elizalde, Johanna Elizabeth (2014)
The purpose of this project was to investigate the reality that cross Ecuadorian companies Tungurahua footwear sector for the subsequent development of viable strategies focused on increasing exports within the sector and specifically those associated with the CALTU companies.